The carcinoid that doesn't select – the role of preoperative echocardiography in carcinoid heart disease - Emese Papp; Mónika Dénes; Anita Zádori; Katalin Takó; Miklós Tóth; Judit Tőke; Jenő Szolnoky; Réka Rácz; Péter Andréka (Cardiologia Hungarica)
Introduction: Carcinoid heart disease (CHD) is associated with neuroendocrine tumours and carcinoid syndrome, most commonly affecting the right heart valves, potentially associated with right heart failure which determines the poor survival. Less commonly, it may also affect the heart valves on the left side. Echocardiography has a primary role in the diagnosis of CHD. Case presentation: A 57-year-old female patient with multiplex endocrine neoplasia type 1, primary bronchial carcinoid tumor, multiple bone-, solitary breast metastasis was referred to the Cardiac Surgery Department of our Institute with severe tricuspid regurgitation (TR). Preoperative transthoracic echocardiography (TTE) showed normal left ventricular systolic function, a dilated right ventricle with preserved systolic function, and rigidly suspended, thickened tricuspid and pulmonary valves with severe TR and pulmonary (PR) regurgitation. In addition, the left heart valves were found to be affected: the leaflets of the aortic valve were also thickened and severe aortic regurgitation was confirmed. In case of the mitral valve, a restrictive, fixed posterior leaflet and a mobile anterior leaflet with moderate-severe mitral regurgitation (MR) were seen. In order to quantify accurately, transesophageal echocardiography (TEE) was performed which confirmed severe MR, and a patent foramen ovale (PFO) was detected. After detailed discussion with the patient, quadruple valve replacement and PFO closure were performed by cardiac surgery. In the early postoperative period, the patient developed bilateral cardiac dysfunction with hemodynamic instability, resulting in the patient's death despite all efforts. Conclusion: CHD is a progressive condition predominantly associated with severe TR and PR. CHD affecting all four valves is rare, but the presence of bronchial carcinoid or PFO may increase the risk of left heart disease. Therefore detailed examination (TTE, TEE) of all four valves, and regular follow-up are essential before cardiac surgery. Timing of cardiac surgery and patient selection requires a multidisciplinary approach.